2017
DOI: 10.1136/archdischild-2016-311908
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for functional constipation in adolescent Nigerians

Abstract: FC is a significant health problem among adolescent Nigerians. The condition is associated with low social class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…Divorce or separation of parents, severe illness in family, and parental job loss were home‐related issues that were associated with FC 21,27 . However, other studies failed to identify this as a predisposing factor 19,25 . Frequent domestic fights, marital disharmony, and sibling rivalry were reported in other studies as factors leading to FC 17,27 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Divorce or separation of parents, severe illness in family, and parental job loss were home‐related issues that were associated with FC 21,27 . However, other studies failed to identify this as a predisposing factor 19,25 . Frequent domestic fights, marital disharmony, and sibling rivalry were reported in other studies as factors leading to FC 17,27 …”
Section: Resultsmentioning
confidence: 98%
“…The stressful events were diverse, and no clear pattern was detectable to make a valid comparison between studies. Three studies included the same list of stressful events 21,25,27 …”
Section: Resultsmentioning
confidence: 99%
“…Although the typical African diet is high in complex carbohydrates and other fiber-rich foods, urbanization has led to much more snacking on high fat/sugary foods in this region [ 29 ]. Epidemiologic studies that have shown that FGIDs are common to school children in Africa [ 30 , 31 ]; however, there is a scarcity of data about dietary interventions for FGIDs in the African continent. Thus, although many of the African foods are high in FODMAPs, and FGID prevalence is high, the association of diet and symptoms has not been investigated to date.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…However, epidemiological research in Asian countries has shown a much higher prevalence of up to 32% according to standard Rome III criteria (2). Similar studies in Africa show a prevalence of 27% in Nigerian school children (3). The highest prevalence noted in Sri Lankan children is 15.5% (4).…”
mentioning
confidence: 94%